2019
DOI: 10.1055/s-0039-1697662
|View full text |Cite
|
Sign up to set email alerts
|

A Thrombin-Activatable Factor X Variant Corrects Hemostasis in a Mouse Model for Hemophilia A

Abstract: Engineered recombinant factor X (FX) variants represent a promising strategy to bypass the tenase complex and restore hemostasis in hemophilia patients. Previously, a thrombin-activatable FX variant with fibrinopeptide-A replacing the activation peptide (FX-delAP/FpA) has been described in this regard. Here we show that FX-delAP/FpA is characterized by a sixfold shorter circulatory half-life compared with wild-type FX, limiting its therapeutical applicability. We therefore designed a variant in which the FpA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Examples include protease-activatable drugs (pro-drugs), antibodies (pro-antibodies), probes for imaging, and conjugates for photodynamic therapy. Notably, thrombin-cleavable drugs are under development to target the activity of the drug at sites where thrombin presents, such as the sites of clot formation, injury, and inflammation [ 44 , 45 , 46 , 47 ]. An example of a thrombin-activatable pharmaceutical closely related to our study (currently in clinical trials) is an EHL FVIII representing a recombinant FVIII genetically fused to the FVIII-binding domain of VWF [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Examples include protease-activatable drugs (pro-drugs), antibodies (pro-antibodies), probes for imaging, and conjugates for photodynamic therapy. Notably, thrombin-cleavable drugs are under development to target the activity of the drug at sites where thrombin presents, such as the sites of clot formation, injury, and inflammation [ 44 , 45 , 46 , 47 ]. An example of a thrombin-activatable pharmaceutical closely related to our study (currently in clinical trials) is an EHL FVIII representing a recombinant FVIII genetically fused to the FVIII-binding domain of VWF [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some recent studies have reported that thrombin-activatable FX mutants enhanced hemostatic activity in in vitro and in vivo in hemophilia models [26,28,29], and the data suggested that FX-containing concentrates could offer the possibility of improved hemostatic treatment in the hemophilia human individuals. Also, previous Japanese studies highlighted the potential efficacy of pd-FVIIa/FX , consisting of a mixture of FVIIa and FX (w:w=1:10), in congenital hemophilia patients with inhibitors and in acquired HA [6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies utilizing in vitro and in vivo model systems have suggested that mutated FX or FXa might be useful for treatment in PwHA [26][27][28][29]. Analyses of binding affinity of emicizumab and FX determined by surface plasmon resonance-based assays have demonstrated, however, that the K d of emicizumab binding to FX was 1.85 μM [30],…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…FX variants (1 µM) and plasma-derived prothrombin (5.6-20 µM) were pretreated with APMSF (100 µM) and incubated for 60 minutes at 37°C in order to allow for the decomposition of unbound inhibitor, thereby preventing interference in the assay. 19 Steady-state initial velocities of macromolecular substrate cleavage were determined discontinuously at 25°C in assay buffer as described. 12 Briefly, unless otherwise stated, progress curves of prothrombin were obtained by incubating PCPS (50 μM), DAPA (10 µM), prothrombin (1.4 µM), and FV810 or v-ptFV (300 nM), and the reaction was initiated with 250 nM of FX, upon which the rate of prothrombin conversion was measured.…”
Section: Prothrombin Activationmentioning
confidence: 99%